The response of impulsively loaded sandwich plates - Farrow, Gary Herbert (Department of Mechanical Engineering, 2016)
This thesis describes a numerical study of the response of impulsively loaded circular sandwich plates using the general purpose finite element programme called ABAQUS. The sandwich plate studied consists of three layers. The two outer layers are of mild steel and the centre layer, or core, is of air. Because of this configuration, the analysis is split into two sections. The first is the study of impulsively loaded circular single plates and the second is the study of the interaction of the outer layers of the sandwich plate on each other. The plates are analysed in the impulse range that results in large plastic deformations known as Mode I Failure. Mode II and III failure of the plates, where failure by tearing occurs, is omitted. The results of the single plate analysis are compared to experimental and analytical work. Criteria for comparison include mid-plate deflections, strain rate dependence, strain predictions, plate thinning, deformation shape and response time. The results of the sandwich plate analysis are compared to experimental data and the criteria for comparison include mid-plate deflections and the diameter of the contact area of the two outer layers. Other aspects of the plate behaviour such as response times and the amount of strain energy absorbed are also discussed. The explicit integration scheme is considered the best finite element solution method to use for this dynamic response problem. The pressure loading model is found to give the best correlation with experimental data while velocity loading models tend to result in instabilities in the explicit solution scheme. The presented results for both the single plates and the sandwich plates show good correlation with the experimental data. In the case of the sandwich plates, the predicted contact diameters show good correlation with the experimental work. The phases of deformation evident in the sandwich plate experimental work are not evident in the presented results, while the mid plate deflection predictions show correct trends, but over estimate the experimental data.